Increasing the capture rates of brushtail possums in Victor #1 leg-hold traps. Issue 2 (3rd April 2022) - Warburton, Bruce; Morriss, Grant; Howard, Simon
ABSTRACT: Leg-hold or foot-hold traps have been used in New Zealand for trapping brushtail possums ( Trichosurus vulpecula ) since the 1920s. In the mid-1990s, when the National Pest Control Agencies (NPCA) developed a national protocol for monitoring possums, they standardised how traps should be set, which lure to use and where to place it. These recommendations aimed to achieve standardisation (important for population monitoring), not necessarily high capture rates. Recent use of trail cameras has revealed possums eating the lure, but then walking away without stepping on the trap, suggesting that modifications to the way traps are set or lured might enable increased capture rates of possums. We compared the capture rate of four alternative trap sets (i.e. double sets, covered traps, hazed traps, enlarged trigger plates) with standard NPCA-recommended sets. None of these modified sets increased the captures rates. We then compared the capture rate of traps with the lure placed on the ground encircling the trap (including a vertical visual lure) against the NPCA-recommended method of placing the lure behind the trap. This modification resulted in a 33% increase in capture rate suggesting modifications to the luring method can increase capture rates and make ground-based possum control more effective.